Visualisasi Kekuatan Mamak pada Zaman Modern dalam Karya Lukis Surealis - Ramadhan, Wanda; Kharisma, Maltha (TSAQOFAH, 2025)
This work, titled Visualizing the Power of Mamak in the Modern Era through Surrealist Painting, aims to depict the role and symbolic strength of the Mamak figure in Minangkabau matrilineal culture through a surrealist art approach. The medium used is oil on canvas, featuring everyday objects portrayed in unconventional and symbol-laden ways in accordance with the characteristics of surrealism. The creation process involved several stages: proposal development, sketch refinement, consultations, painting execution, and final finishing. This artwork seeks to elevate traditional cultural values that remain relevant in the modern era while offering a creative and profound visual interpretation. The resulting artistic findings are expected to contribute to cultural preservation and the advancement of contemporary visual art in Indonesia.